Workplace Bullying, Anxiety, and Job Performance: Choosing Between “Passive Resistance” or “Swallowing the Insult”? - Wu, Mengyun; He, Qi; Imran, Muhammad; Fu, Jingtao (Frontiers in Psychology, 2020)
Anxiety arising from workplace bullying is a key concern for job performance. Anxiety can explain the effects of workplace bullying: individuals may seek to deal with their anxiety by applying specific behaviors. However, anxiety research does not carefully distinguish between state anxiety and trait anxiety, and so the impact of anxiety in general has been seen as complex and contradictory. Individuals may respond to bullying and anxiety through “passive resistance” or by “swallowing the insult”. But under what circumstances do individuals choose between these options? This paper summarizes the mechanisms of state anxiety and trait anxiety and uses cognitive balance theory to measure loss of self-control and the strategic choices. A moderated mediation model is presented for the relationship between workplace bullying and job performance using key variables of state anxiety and trait anxiety. Employee-supervisor pairs from 20 organizations and institutions from Tianjin, Jiangsu and Hainan participated in a two-point longitudinal survey in 2019, 82.67% effective. Analysis verified that trait anxiety is the decisive perspective for choosing between “passive resistance” and “swallowing the insult”. This provides theoretical and practical contributions to psychology and organizational behavior research.